TEKNOLOGI PENGOLAHAN PAKAN DI DESA DUKUHBADAG KECAMATAN CIBINGBIN KABUPATEN KUNINGAN - Fitri Dian Perwitasari; Devi Yuliananda; Bastoni Bastoni; Mus Nilamcaya; Arie Susetio Utami (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Universitas Muhammadiyah Cirebon, 2019)
Community service activities in the form of training and assistance in increasing awareness of the importance of feed management through extension activities (2) activities, namely: 1. Socialization, 2. Training and Mentoring. This training and mentoring aims to increase knowledge and skills to farmers in Dukuhbadag Village, Cibingbin Regency Kuningan District. The addition of knowledge and skills in Feed Processing Technology is expected to increase livestock production. The targets in this PPM activity are farmers in the village of Dukuhbadag, Cibingbin Regency Kuningan District. The method of activity in this service program consists of 2 activities: training and mentoring. 1) dissemination activities in the form of small-scale material and practices to farmers, 2) training and mentoring namely activities carried out after the training activities were carried out by conducting initial surveys, interviews and large-scale practices involving farmers. The results of this study with a positive response by supporting our activities are providing the availability of counseling places, participants' enthusiasm, the support of the Village Head of Dukuhbadag, government officials, farmer groups and each member of the PPM. The obstacles faced are limited time, place and budget so that this activity has not 100% stimulated farmers to implement this appropriate technology. The benefits that can be obtained by participants in the PPM activity include additional knowledge about Feed Management in the Dukuhbadag Village, Cibingbin Regency Kuningan District. Keywords: Silase, Breeders and Dukuhbadag Village